Ludo Disaster Alert Educational Game as A Disaster Preparedness Education Strategy at Setonorejo 1 Kras Elementary School - Fidiana Kurniawati; Vitaria Wahyu Astuti (STIKes Patria Husada Blitar, 2023)
Children are one of the most vulnerable groups at risk of being affected by a disaster because they are triggered by a limited understanding of the risks around them, which results in a lack of preparedness in dealing with disasters. Disaster preparedness is needed within the scope of the education unit so that from an early age, the community, especially children. The design of educational media with games is an effective way of educating children learning about disasters. The aims to analyze the effect of the ludo disaster alert educational game as a disaster preparedness education strategy at Setonorejo 1 Kras Elementary School. The research design used was pre-experimental using the one group pre-test post-test design method. The population were 20 students of Setonorejo 1 Kras Elementary School who met the inclusion criteria using a total sampling technique. The inclusion criteria were children aged 8-9 years, children who came to school during data collection and children who were willing to be examined. Data analysis used Wilcoxon. Before being given the educational game of ludo disaster alert students were in the almost prepared category (40%), and after the educational game of ludo disaster alert there was an increase in preparedness with 55% of respondents having the very prepared category. There was a significant difference between before and after the educational game ludo disaster alert with a significance value of 0.000 (p <0.05). Ludo disaster alert educational game has an effect on student disaster preparedness at Setonorejo 1 Kras Elementary School